Swan research and conservation: a synthesis of information presented at the 7th International Swan Symposium - Rees, Eileen C.; Clausen, Preben (Wildfowl, 2024)
Detailed studies of swans Cygnus sp. have been undertaken since the mid-20th century, with results of research programmes presented periodically at international symposia since the 1st International Swan Symposium was held in the UK in 1971. Here, we introduce the proceedings of the 7th International Swan Symposium (7th ISS) of the IUCN SSC Swan Specialist Group, held at Jackson, Wyoming in October 2022, by providing an overview of the latest information on swan populations presented at the meeting, published as papers in this issue and in other journals. The symposium was held in conjunction with the 26th Conference of the Trumpeter Swan Society and was hosted and co-organised by the Ricketts Conservation Foundation. Presentations covered a range of topics including population monitoring, movements and flyway delineation, habitat use, demographic rates, climate change, threats and conservation management of the species. As for the 6th ISS, held in Estonia in 2018, Southern Hemisphere swans were under-represented at the 7th ISS, but greater efforts will be made to cover these species more effectively, along with continued monitoring and assessment of swan populations in the Northern Hemisphere, ahead of the next International Swan Symposium in c. 2–3 years’ time.